Proposed Business Strategy For Sakola Motekar In Ciamis To Increase Profit - Widjanarko, Ignatius Aldo (Action Research Literate, 2024)
This study examines the development of a sustainable business strategy for Sakola Motekar, a non-formal educational institution in Sukajadi village, Ciamis Regency, aimed at enhancing profitability. The research addresses significant financial challenges faced by Sakola Motekar, primarily due to its reliance on unstable donations, which threaten operational continuity. In the context of Industry 4.0, securing sustainable income streams is crucial for institutions like Sakola Motekar to continue delivering essential educational services. The research combines qualitative analysis and strategic management tools to develop actionable strategies. Data was collected through semi-structured interviews with key stakeholders and supplemented with secondary data from literature and organizational documents. The analysis involves a thorough internal and external assessment using the Resource-Based View (RBV), VRIO framework, PESTEL analysis, and Porter's Five Forces model, leading to strategic recommendations. Key findings reveal that Sakola Motekar has valuable resources, including strong community engagement, unique educational programs, and established networks. However, challenges include inadequate financial management and over-reliance on volunteer staff. External opportunities include growing demand for non-formal education in rural areas and potential digital expansion, while threats involve regulatory compliance and competition. The proposed strategy includes enhancing financial management, diversifying revenue through commercialization of educational programs, and leveraging strategic partnerships. A formalized marketing approach and structured volunteer management system are also recommended. The expected outcome is a stabilized financial foundation for Sakola Motekar, enabling it to expand its impact and continue serving the community. This research contributes to educational business management by offering a practical framework for non-formal schools to achieve financial sustainability while maintaining their educational mission